PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE TEAMS GAMES TOURNAMENT TERHADAP HASIL BELAJAR SISWA PADA MATERI HIMPUNAN (Di kelas VII SMPN 1 CibadakKabupatenLebak) - Linda Linda; Mia Rusmiati (Cakrawala Pedagogik, 2020)
Abstract This research is a quasi-experimental research with pretest-posttest control group design. The population of this study were all students of class VII at SMPN 1 CibadakLebak Regency as many as 9 classes with a total of 280 students. The sample in this study was selected 2 classes by purposive sampling, namely class VII-C (experimental class) and VII-B (control class). The data collection technique in this study was carried out through tests, in the form of 5 objective description questions. The research data were analyzed using the Mann Whitney test and SPSS 20.0. The results of the Post Test in the experimental class which were given teaching with the Teams Games Tournament type of cooperative learning model obtained an average student learning outcomes on the set material of 72.31. Meanwhile, the control class taught by conventional learning methods obtained an average result of 59.7. Based on the results of hypothesis testing using the Mann Whitney test, it was found that Z_hitung = 2.21 and Ztable = 1.645 at the significant level a = 0.05, then Z_count>Ztable (2.21> 1.645), then H_0 was rejected and H_1 was accepted. Then according to the test using the SPSS 20.0 Sig (2-tailed) 0.017 <significant level (0.05), then H_0 is rejected and H_1 is accepted. From these two tests, it can be concluded that student learning outcomes on set material using the Teams Games Tournament type of cooperative learning model are higher than student learning outcomes on set material using conventional learning methods. Thus the cooperative learning model type Teams Games Tournament has an effect on student learning outcomes on set material.